北京山区沟域经济发展的空间结构 - 张义丰; 贾大猛; 张宏业; 谭杰; 宋思雨; 孙瑞峰 (地理学报（英文版）, 2011)
F127; Valley economy is a new mode in mountainous area development that is defined by various characters of valley development, and is a distinguishing economical geographic pattern for mountainous area development. The special spatial coupling relations in the dis-tribution of different mountainous elements in valleys are new subjects for the mountain de-velopment studies, and such studies are meaningful both for researches and practices.Based on the long term researches on mountainous area development and following a brief exploration into the connotations and the spatial organizing process of valley economy, the authors analyzed the present situations of the development of valley economy in Beijing'smountainous areas, studied the characteristics and the impacts of the spatial structural changes of the valley economy in Beijing's mountainous areas, and finally proposed a rational arrangement of the spatial structure of the valley economy in Beijing's mountainous areas. It is considered in this study that va